2002
DOI: 10.1104/pp.010643
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Photosystem II Carbonic Anhydrase in Maize Mesophyll Chloroplasts

Abstract: One form of carbonic anhydrase (CA) has been observed in maize (Zea mays) thylakoids and photosystem II (PSII)-enriched membranes. Here, we show that an antibody produced against a thylakoid lumen-targeted CA found in Chlamydomonas reinhardtii reacts with a single 33-kD polypeptide in maize thylakoids. With immunoblot analysis, we found that this single polypeptide could be identified only in mesophyll thylakoids and derived PSII membranes, but not in bundle sheath thylakoids. Likewise, a CA activity assay con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…With both PSII membrane preparations, from pea and wheat, the CA-activities of supernatants after sedimentation of membranes treated either with Triton X-100 or CaCl 2 were not detected. Lu and Stemler [4] observed CA activity in the supernatants after the similar salt treatment of PSII membranes, after desalting of these supernatants. The absence of CA activity in the supernatants, that were not desalted ( Table 1), showed that an increase of CA activity in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With both PSII membrane preparations, from pea and wheat, the CA-activities of supernatants after sedimentation of membranes treated either with Triton X-100 or CaCl 2 were not detected. Lu and Stemler [4] observed CA activity in the supernatants after the similar salt treatment of PSII membranes, after desalting of these supernatants. The absence of CA activity in the supernatants, that were not desalted ( Table 1), showed that an increase of CA activity in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Mn-stabilizing protein 33 kD was considered as a possible carrier of the CA activity [4]. However, this protein passes into solution in the course of CaCl 2 treatment of PSII membranes [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A low level of carbonic anhydrase (CA) activity, more than 10 3 slower than typical Zn 2+ -CA, has been found to be intrinsic to oxygenevolving PS II membranes [69,70]. A soluble CA activity was found associated with the 33 kDa extrinsic protein of PS II (PsbO) and depends on the concentration of Mn 2+ and Cl − .…”
Section: Bicarbonate Ion-bicarbonatementioning
confidence: 99%
“…There is an evidence that PS II-associated CA generates bicarbonate ions at a rate sufficient to bound protons released in the inner space of thylakoid in the process of photosynthetic oxidation of water [9]. Hence, CA prevents acidic denaturation of manganese cluster of PS II, as critical increase in local H + concentration may damage the active centers of the complex and result in their destruction with manganese release in liquid environment [10,11].…”
mentioning
confidence: 99%